1969
DOI: 10.1139/v69-428
|View full text |Cite
|
Sign up to set email alerts
|

Calculated R.R.K.M. unimolecular dissociation rate constants for hydrazine

Abstract: Unimolecular rate constants for hydrazine dissociation by thermal and chemical activation have been calculated according to the R.R.K.M. theory. The two activated complex models used in the calculations represent plausible upper and lower bounds to the rate constants. The calculations are mainly directed toward establishing expected decomposition to stablilization ratios of N,H4 produced by combination of NH, radicals; however, a general comparison to available experimental data for hydrazine dissociation is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…= 1 X 10 -xø cm 3 s -x. On the other hand, theoretical studies, such as the RRKM calculations of Sester and Richardson [1969], indicated that the high pressure limit was attained only above 1000 torrs, an indication agreeing well with the fact that the thermal decomposition of hydrazine also has a high pressure limit [Benson and O'Neal, 1970]. A recent experimental investigation of Miller [1973] confirms the theoretical expectations, and K•.…”
Section: Photolysis Of Ammonia B•y the Solar Radiations With 2 >mentioning
confidence: 52%
“…= 1 X 10 -xø cm 3 s -x. On the other hand, theoretical studies, such as the RRKM calculations of Sester and Richardson [1969], indicated that the high pressure limit was attained only above 1000 torrs, an indication agreeing well with the fact that the thermal decomposition of hydrazine also has a high pressure limit [Benson and O'Neal, 1970]. A recent experimental investigation of Miller [1973] confirms the theoretical expectations, and K•.…”
Section: Photolysis Of Ammonia B•y the Solar Radiations With 2 >mentioning
confidence: 52%